Hydrocele Rupture during Sexual Intercourse: a Case Report and Review of the Literature - Deniz Bolat; Anıl Eker; Hamza Eren Güzel; Tansu Değirmenci (Journal of Urological Surgery, 2020)

(untitled)
Hydrocele rupture is a rarely seen situation in clinical practice. Due to the limited number of cases in the literature, management of hydrocele rupture is controversial. A 34-year-old male patient with a history of untreated idiopathic 10x9 cm right hydrocele for one year was admitted to the emergency department with the complaints of right hemiscrotal pain and ecchymosis after a sexual intercourse. In this paper, we present our approach to a patient with hydrocele rupture developing during sexual intercourse.